Perceraian di Kabupaten Rembang - Erinda Larasati; Nurhadi Nurhadi; Yuhastina Yuhastina (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Divorce research in Rembang Regency, Central Java aims to explore the study of bickering factors that can be a way of ending a marital relationship. The method used is a combination of quantitative and qualitative. Quantitative data obtained through surveys with purposive sampling techniques. Researchers selected 30 divorced people as respondents. Qualitative data was obtained through in-depth interviews with 10 potential participants. Qualitative data is analyzed using Spradley's domain model, which provides an overview of and thoroughly of the research object. The data obtained through surveys and interviews is subsequently converted into a script in order to obtain an overview of the objects studied.  The study concluded that the factors that cause quarrels in the family are (1) the inability to support the family; (2) infidelity; (3) Domestic Violence; (4) misunderstanding; and (5) mismatch with a partner due to matchmaking practice.